Use and Effectiveness of the Cadaver-Lab in Orthopaedic and Traumatology Education: An Italian Survey - Losco, Michele; Familiari, Filippo; Giron, Francesco; Papalia, Rocco (Joints, 2017)
Purpose The purpose of this study is to provide basic information on the availability and current use of cadaver laboratories in the education of orthopaedic residents and trainees and to determine the interest for the implementation of this type of training.Methods All Orthopaedic residents and trainees who attended a cadaver laboratory organized by SIGASCOT (Italian Society of the Knee, Arthroscopy, Sports Traumatology, Cartilage and Orthopaedic Technology) between 2013 and 2016 were asked to complete a survey on the availability and current use of cadaver laboratories in the education of Orthopaedic residents and trainees. The survey was sent via e-mail to 102 Orthopaedic residents and trainees. All data were analyzed and all responses are presented as counts, percentages, or means.Results Thirty-eight (37.2%) Orthopaedics and traumatology residents and trainees completed the survey and were included in this analysis. Eighteen trainees (18/38; 44.3%) attended a cadaver laboratory focused on lower limb surgery, whereas 20 (20/38; 52.7%) on upper limb surgery. Twenty participants (55.7%) perceived skills laboratory sessions as extremely beneficial to the understanding and becoming familiar with the normal surgical anatomy; moreover, 16 (45.7%) participants considered the cadaver laboratory extremely beneficial to the understanding of a specific surgical technique and very beneficial (44.4%) to become confident with arthroscopic or other specific surgical instruments. Over 60% of participants perceived cadaver laboratory to be very to extremely beneficial to increase confidence and speed in the operating room (OR), and more than a half of them considered skills laboratory sessions to be extremely beneficial to increase participation and decrease the occurrence of damages in the real surgical activity.Conclusion Orthopaedic residents and trainees found the addition of a cadaver laboratory for teaching surgical skills a significant benefit to both their overall education and surgical skills training.Level of Evidence Level IV, survey study.
Keywords: orthopaedics; residents' training; survey; cadaver laboratory